The influence of seated exercises on balance, mobility, and cardiometabolic health outcomes in individuals living with a stroke: A systematic review and meta-analysis. (July 2023) - Mackie, Paul; Eng, Janice J
Objective: Seated exercises could prove a safe alternative to traditional weight-bearing exercises in stroke, but its effects on mobility and modifiable risk factors of stroke are limited. The objective is to investigate the effects of seated exercises on balance, mobility, and cardiometabolic health in individuals living with a stroke. Data sources: Medline, EMBASE, CINAHL, and Cochrane library were searched up to October 2022, in addition to the 2018 Evidence-Based Review of Stroke Rehabilitation. Methods: Trials that incorporated predominantly seated exercises and outcomes of balance, mobility, or cardiometabolic health in those living with a stroke were included. Quality assessments of randomized controlled trials were done using the Cochrane Risk-of-Bias Tool. Results: Seven trials were included in the review ( n = 337) with five trials including participants < 6 months post-stroke. Seated exercises improved balance (standard mean difference (SMD) = 0.76; 95% confidence interval (CI), 0.50, 1.02) and mobility (SMD = 0.68; 95% CI, 0.24, 1.13) outcomes compared with control. Sensitivity analysis of gait speed found no significant change (mean difference (MD) = 0.33 m/s; 95% CI, −0.23, 0.89) following seated exercises compared with control. One trial found no significant changes in blood pressure. Most trials (78%) were assessed as having some concern for bias. Conclusion: These findings suggest beneficial effects of seated exercises on balance and mobility outcomes in those with a stroke, compared with standard therapy or an attention control. However, there is limited evidence on the effects of seated exercises on outcomes of cardiometabolic health, particularly prominent modifiable risk factors for stroke. PROSPERO registration number: CRD42022307426.